Comparison of apical sealing ability between bioceramic and zinc oxide eugenol-based sealer during root canal treatment, in vitro - Dedy Agoes Mahendra; Yora Nindita; Gustantyo Wahyu Wibowo; Gloria Fortuna (Majalah Kedokteran Gigi Indonesia, 2022)
Obturation with a sealer material that provides an adequate apical sealing ability is required to prevent endodontic treatment failure due to microleakage. However, there are no sealers that meet all the physical and chemical properties to be able to hermetically seal the root canal system to date. Various sealer materials have been developed in recent years including the use of bioceramic materials which are claimed to have excellent biocompatibility to tissues. This study aimed to compare the apical sealing ability of bioceramic-based and zinc oxide eugenol (ZOE)-based sealer in root canal treatment. A total of 27 extracted mandibular premolars were decoronated to the standard root length of 14 mm. The root canals were prepared with a crown-down technique using manual instrument to file F3 (30/.09). The samples were then divided into three groups: obturation with bioceramic-based sealer (n=9); ZOE-based sealer (n=9); and control group (n=9). Microleakage was measured using a dye penetration method with 1% methylene blue and observed under stereomicroscope at x20 magnification. The mean of the maximum penetration length from the lowest to the highest was found in the bioceramic-based sealer group (0.825 mm), the ZOE-based sealer group (3.850 mm), and the control group (4.444 mm). One-way ANOVA test showed a significant difference in the maximum penetration length between the three groups (p<0.05). The post hoc LSD test showed a significant difference in the maximum penetration length between the bioceramic-based and ZOE-based sealer groups (p<0.001). Obturation with bioceramic-based sealer provides a better apical sealing ability than that with ZOE-based sealer.